Environmental ethics from the Qur'nic philosophy - Samsudin, Sofiah; Islam, Md Sirajul (American-Eurasian Network for Scientific Information, 2014)
The Environmental Ethics (EE) refers to the justice of human beings with non-human beings as well as rule to Development of the Natural Environment (DNE). In fact, safety of the environment is a big challenge of the 21st century for environmentalists. Indeed, not only the natural ecologists responsible for save of environment, but also everybody can contribute through follow the EE. The main objectives of this study obtain knowledge about the Creator and creatures. Then show the relationship among the Creator, creatures and humans. Consequently, we will be more motivate for environmental issues, this motivation lead us to be more sensible about the EE, then through apply the EE in our daily life environment will be improve. However, this study focuses on the Qur'anic statement on the EE. As a result, the study found that the Almighty Allah SWT creates the universe strangely perfect by His will based on the judgment. Everything is playing their important role in the chain of ecosystems. Allah made them as much as coherence and consistency among them. To some up, every creature in the universe is ecological interconnected. Hence, humans should be justice as well as sympathetic with each and every component of the environment. Because, if anybody do unjust to any constituent of environment other constituents will take action from us to be change their original nature.